Habituation of Discipline on Time Learning Indonesian Language for Slow Learner Students in Elementary School - Ramadhani, Fitri Yana Nia; Sutama, S (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study examines strategies for habituating punctuality discipline among slow‑learner students in Indonesian language classes at State Elementary School 4 Pilangpayung. By focusing on how timely‑discipline practices can support learners who progress more slowly, the research aims to identify effective teacher‑led interventions that enhance these students’ engagement and mastery of Bahasa Indonesia under the Merdeka Curriculum. Methodology: Adopting a qualitative case‑study design, the investigation employed in‑depth interviews with teachers, observations of classroom routines, and analysis of school documentation. Researchers immersed themselves in the daily learning environment to capture detailed descriptions of slow‑learner characteristics, the implementation of punctuality‑habituation tactics, and the broader instructional processes at work. Results: Findings reveal that teachers successfully embed punctuality discipline by integrating Merdeka‑aligned lessons with consistent time‑management cues, employing individualized learning approaches, and engaging parents as partners in reinforcing routines at home. Key enablers include active principal supervision of discipline activities, students’ own growing awareness of timeliness, and teachers’ hands‑on involvement. Conversely, limited student self‑awareness and unsupportive home or community environments were identified as barriers to consistent punctuality. Applications/Originality/Value: By mapping these strategies and contextual factors, the study offers practical guidance for educators seeking to strengthen time‑discipline habits among slower learners. Its insights emphasize the importance of combining curriculum‑aligned classroom practices, personalized support, and family collaboration. Education leaders can use these findings to design targeted training programs and parent‑engagement initiatives that foster punctuality, thereby improving learning outcomes for all students